RhoA/Rho-kinase activation promotes lung fibrosis in an animal model of systemic sclerosis. (2nd January 2016) - Bei, Yihua; Hua-Huy, Thong; Nicco, Carole; Duong-Quy, Sy; Le-Dong, Nhat-Nam; Tiev, Kiet-Phong; Chéreau, Christiane; Batteux, Frédéric; Dinh-Xuan, Anh Tuan
ABSTRACT: Background: Systemic sclerosis (SSc) is a connective-tissue disease characterized by vascular injury, immune-system disorders, and excessive fibrosis of the skin and multiple internal organs. Recent reports found that RhoA/Rho-kinase (ROCK) pathway is implicated in various fibrogenic diseases. Intradermal injection of hypochlorous acid (HOCl)-generating solution induced inflammation, autoimmune activation, and fibrosis, mimicking the cutaneous diffuse form of SSc in humans. Our study aimed firstly to describe pulmonary inflammation and fibrosis induced by HOCl in mice, and secondly to determine whether fasudil, a selective inhibitor of ROCK, could prevent lung and skin fibroses in HOCl-injected mice.Methods: Female C57BL/6 mice received daily intradermal injection of hypochlorous acid (HOCl) for 6 weeks to induce SSc, with and without daily treatment with fasudil (30 mg·kg −1 ·day −1 ) by oral gavage.Results: HOCl intoxication induced significant lung inflammation (macrophages and neutrophils infiltration), and fibrosis. These modifications were prevented by fasudil treatment. Simultaneously, HOCl enhanced ROCK activity in lung and skin tissues. Inhibition of ROCK reduced skin fibrosis, expression of α-smooth-muscle actin and 3-nitrotyrosine, as well as the activity of ROCK in the fibrotic skin of HOCl-treated mice, through inhibition of phosphorylation of Smad2/3 and ERK1/2. Fasudil significantly decreased the serum levels of anti-DNA-topoisomerase-1 antibodies in mice with HOCl-induced SSc.Conclusions: Our findings confirm HOCl-induced pulmonary inflammation and fibrosis in mice, and provide further evidence for a key role of RhoA/ROCK pathway in several pathological processes of experimental SSc. Fasudil could be a promising therapeutic approach for the treatment of SSc.